Promotion without commitment: Signaling, time inconsistency and decentralization of the firm - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2012)
This paper explores the consequences and implications of the dual role of promotion in an environment where a firm must simultaneously achieve two distinct goals - assignment and incentive provision - via the strategic use of promotions. We argue that the efficient promotion rule is generally not implementable, as it necessarily entails timeinconsistent objectives: the firm is always tempted ex post to promote the worker with the highest upside potential rather than the one with the highest output. This ex post bias towards the assignment role of promotion leads to inefficient task choices where too many workers are induced to work on the difficult task to signal their productivities. The framework identifies the costs and benefits of decentralization, in relation to factors such as the levels of human and social capital, the degree of market competition, firm size, and distance to the technology frontier, and provides predictions that are in line with recent empirical evidence.
Keywords: D82; M51; 330; Assignment; Incentive provision; Tournament; Promotion; Commitment; Time inconsistency; Personalmanagement; Leistungsanreiz; Zeitkonsistenz; Entscheidungstheorie